(untitled) (Bangladesh Journal of Botany, 2026)
This study aims to determine the germination and seedling growth responses of silage maize (Zea mays L.) under different levels of drought stress, in order to identify sensitive and tolerant cultivars. Nine different silage maize cultivars (Samada 07, Hido, Bodega, DKC 7240, AGA, Hacıbey, Pioneer 2105, M16S45 and PR32W86) were used. Drought stress conditions (0, 5, 10, 15 and 20%) were provided using polyethylene glycol (PEG-6000) material. Statistically significant (p<0.01) differences were found between varieties and drought levels in terms of all germination and seedling development parameters. As a result, the negative effects of drought stress were observed at 10-15% drought levels in germination traits and at 5% drought level in seedling growth parameters. Among the silage maize cultivars, AGA stood out for its higher tolerance in terms of germination traits, while M16S45 was more tolerant in terms of seedling growth parameters compared to the other cultivars. Bangladesh J. Bot. 55(1): 107-114, 2026 (March)